Whatever happened to Lori Lovely? : a novel - McCoy, Sarah, 1980- (William Morrow, an imprint of HarperCollinsPublishers, 2025)
"In 1969 twenty-three-year-old starlet Lori Lovely, the apple of Hollywood's eye, shocks the world by ditching a promising film career to take vows of poverty, chastity, and obedience as a Benedictine nun. Gossip columnists and scandal sheets can't get enough of the story. Why would a successful starlet take the veil? Was she hiding from someone? Did it have anything to do with the tragic death of her costar, heartthrob singer Lucas Wesley? In 1990 Lu Tibbott is under the gun to complete her senior thesis in modern American history. Instead of spending weeks in dusty archives, Lu decides to dig into a true twentieth-century mystery and write about her aunt Lori, now the Mother Abbess at a cloistered convent in rural New England. Biographers, bloggers, and media types have long speculated about her aunt's sudden departure from Hollywood. Mother Lori, however, has refused all requests for interviews-until Lu arrives at the abbey with a tape recorder in hand. To her delight, Mother Lori announces she's finally ready to talk...but only if Lu is truly ready to listen?" --